2020
DOI: 10.3389/fimmu.2020.00713
|View full text |Cite
|
Sign up to set email alerts
|

Redirection of Cord Blood T Cells and Natural Killer Cells for Elimination of Autologous HIV-1-Infected Target Cells Using Bispecific DART® Molecules

Abstract: Mother-to-child transmission of HIV-1 remains a major global health challenge. Currently, HIV-1-infected infants require strict lifelong adherence to antiretroviral therapy to prevent replication of virus from reservoirs of infected cells, and to halt progression of disease. There is a critical need for immune interventions that can be deployed shortly after infection to eliminate HIV-1-infected cells in order to promote long-term remission of viremia, or to potentially cure pediatric HIV-1-infection. Bispecif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 74 publications
2
6
0
Order By: Relevance
“…Both markers of ADCC activity were enhanced when NK cells were preincubated with IL-15 ( Fig. 8C-D ), consistent with prior literature indicating that IL-15 augments neonatal NK cell cytotoxicity (Pollara et al, 2020). Next, we assessed the capacity of cord blood CD8+ T cells to mediate Fc-dependent antibody effector functions.…”
Section: Resultssupporting
confidence: 91%
“…Both markers of ADCC activity were enhanced when NK cells were preincubated with IL-15 ( Fig. 8C-D ), consistent with prior literature indicating that IL-15 augments neonatal NK cell cytotoxicity (Pollara et al, 2020). Next, we assessed the capacity of cord blood CD8+ T cells to mediate Fc-dependent antibody effector functions.…”
Section: Resultssupporting
confidence: 91%
“…However, NKG2C + NK-cell expansion also requires costimulation in the form of proinflammatory cytokines, particularly IL-12 [ 16 , 45 ]. IL-12 is under tight epigenetic control in the tolerogenic immune environment maintained throughout gestation [ 46 ], and stimulation of cord blood NK cells with IL-12 and IL-15 has been shown to rapidly increase their functional capacity to levels approaching that of adult NK cells [ 29 , 47 , 48 ]. Thus, it is possible that the restricted cytokine environment in utero hinders expansion of fetal NKG2C + NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…7B2 x anti-CD16A DART molecules were tested for ability to redirect adult PBMCs or cord blood mononuclear cells (CBMCs) to lyse HIV-1-infected CD4 + T cells. 66 The subset of cytotoxic CD56 dim CD16 + NK cells was the dominant population of NK cells in both cord blood and adult PBMC and treatment with IL-15 increased the activation (upregulated HLA-DR and CD69) of NK cells in adult PBMC and cord blood. However, NK cells in cord blood are less mature, less lymphoid homing, less active and produce less granzyme B compared to NK cells in adult PBMCs.…”
Section: Bispecific Cd16a-engaging Moleculesmentioning
confidence: 92%
“…To explore the possibility that DART molecules could be utilized early after birth to eliminate HIV-infected cells and, ultimately, impact persistent infection, Pollara and collaborators evaluated the potency of A32 x anti-CD3 and 7B2 x anti-CD3 DART molecules in the newborn population by analyzing the killing capacity of cytotoxic T cells isolated from the cord blood. 55 Their study revealed that DART molecules were indeed capable of redirecting CD3 + cytotoxic T cells to kill HIV-infected CD4 + T cells. However, cellular subsets acquired from cord blood were less potent than those isolated from the adult peripheral blood, indicating a possible limitation of this strategy.…”
Section: Preclinical and Clinical Studies With Mgd014 And Mgd020mentioning
confidence: 99%